The Model and Structure of the Slovak Catholic Police Chaplaincy - Író, Sándor (Magyar Rendészet, 2019)
This study introduces the military ordinariate that was created to provide pastoral care for the members of the army and the forces of law and order of the Slovak Republic; it analyses and examines the organisational structure and tasks of it. Policemen during their police work have to face many issues (such as fatal accidents, homicide, burnout, the thought of leaving the field, corruption, personal problems, the question of weapon-holding, personal and social prejudice, suicide, racism) that they cannot understand, process or handle effectively. In such cases they need help. Police Chaplaincy services work in many countries inside the institutional framework effectively helping the job of the police. The institutional background and structure of the Slovak Police Chaplaincy must be examined, considering that Hungary’s and Slovakia’s historical and cultural traditions are closely related, so during the build-up of the Hungarian Police Chaplaincy, this can provide useful guidance for the ecclesiastical and state leaders.